A business plan for the start up of a sustainable phone case business with Nusantara inspired designs in Malaysia - Ratha Krishnan, Ragavendra (2025)
NusaCraft Design is a pioneering Malaysian company dedicated to manufacturing and retailing premium phone cases that seamlessly blend of sustainability with cultural heritage. Our products are crafted using injection moulding technology and recyclable plastics, ensuring minimal environmental impact while incorporating traditional Nusantara designs inspired by the rich cultural legacy of Southeast Asia. NusaCraft Design targets eco-conscious consumers and those with an appreciation for heritage aesthetics, offering a unique value proposition in the tech accessories market. Our competitive advantage lies in our commitment to sustainable production, the infusion of cultural artistry, and an affordable pricing strategy that appeals to a broad demographic.